Theoretical study of electron exchange in Mg2+–B collisions. (11th February 2015) - Amami, M; Zaidi, A; Moussa, A; Lahmar, S; Bacchus-Montabonel, M-C
Abstract: The electron capture of Mg 2+ ions in collisions with boron atoms has been investigated using ab initio quantum chemical approaches. The potential energies of the electronic states implicated in the process together with the non adiabatic coupling matrix elements have been calculated by multi-reference configuration interaction methods. Total and partial cross sections for the charge transfer reaction are determined in the (1–600) keV impact energy range by means of semi-classical approaches. A detailed analysis of the electron capture mechanism taking into account radial and rotational interactions has been performed and compared to previous studies on collision systems involving the Mg 2+ projectile ion.